Characterization of clinically isolated thymidine‐dependent small‐colony variants ofEscherichia coliproducing extended‐spectrum β‐lactamase. Issue 1 (January 2018) - Negishi, Tatsuya; Matsumoto, Takehisa; Horiuchi, Kazuki; Kasuga, Eriko; Natori, Tatsuya; Matsuoka, Mina; Ogiwara, Naoko; Sugano, Mitsutoshi; Uehara, Takeshi; Nagano, Noriyuki; Honda, Takayuki
Abstract : Purpose. : Thymidine‐dependent small‐colony variants (TD‐SCVs) are difficult to detect or test for antimicrobial susceptibility. We investigated the characteristics of clonal TD‐SCVs of Escherichia coli, both with and without bla CTX‐M‐3, isolated from a patient. Methodology. : Mutation in the thyA gene was analysed by sequencing, and morphological abnormalities in the colonies and cells of the isolates were examined. Additionally, conjugational transfer experiments were performed to prove the horizontal transferability of plasmids harbouring resistance genes. Results. : The TD‐SCVs contained a single nucleotide substitution in the thyA gene, c.62G>A, corresponding to p.Arg21His. Morphologically, their colonies were more translucent and flattened than those of the wild‐type strain. In addition, cells of the TD‐SCVs were swollen and elongated, sometimes with abnormal and incomplete divisions; a large amount of cell debris was also observed. Changing c.62G>A back to the wild‐type sequence reversed these abnormalities. Conjugational transfer experiments showed that the TD‐SCV of E. coli with bla CTX‐M‐3 failed to transfer bla CTX‐M‐3 to E. coli CSH2. However, the TD‐SCV of E. coli without bla CTX‐M‐3 experimentally received the plasmid encoding bla SHV‐18 from Klebsiella pneumoniae ATCC 700603 and transferred it to E. coli CSH2. Conclusion. : Mutation in the thyA gene causes morphological abnormalities in the colonies and cells of E. coli, as well as inducing thymidine auxotrophy. In addition, TD‐SCVs horizontally transmit plasmids encoding resistance genes. It is important to detect TD‐SCVs based on their characteristics because they serve as reservoirs of transferable antibiotic resistance plasmids.